Webs of Power: Women, Kin, and Community in a Sumatran Village - Blackwood, Evelyn (Rowman & Littlefield Publishers, 2000)
Webs of Power offers a fresh perspective on women in Southeast Asia. Focusing on one rural Minangkabau village, the book provides vital insights into the gendered processes of post-coloniality. The Minangkabau living in West Sumatra are the largest matrilineal group in the world. They have intrigued generations of scholars because they are matrilineal and Islamic. By exploring the contestations and accommodations women and men make with state and Islamic ideologies, Webs of Power discloses the processes at the heart of globalization as well as the complexities of kinship and power in a rural agricultural community. The book challenges conventional thinking about matriliny, showing the prominence of senior women in all aspects of village life.